The Relationship Between Early Breastfeeding Initiation and Exclusive Breastfeeding with the Incidence of Wasting 6-24 Months in the Working Area of the Langsa City Health Center UPTD - Cut Muntia; Debora Simamora; Desi Kisna Wati; Dewi Ratnasari; Mauzatul Hasanah; Tiarnida Nababan (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Wasting in children, especially toddlers, is a worldwide health problem and indirectly causes nutritional deficiencies that will affect the health of growth, disease or infection, and intellectual intelligence of children. This study aims to determine the relationship between early initiation of breastfeeding and exclusive breastfeeding with the incidence of wasting 6-24 months in the Working Area of ??UPTD Langsa City Health Center. This study design uses a cross-sectional analytic type. The population of this study were all mothers who had babies aged 6-24 months totaling 130 people. The research sample used was 56 respondents with a purposive sampling technique. Data analysis was carried out univariately and bivariately using the chi square test. The results of the study showed that there was a relationship between early initiation of breastfeeding with the incidence of wasting 6-24 months with a p-value of 0.045 (p <0.05) and there was a relationship between exclusive breastfeeding with the incidence of wasting 6-24 months with a p-value of 0.041 (p <0.05). There is a relationship between early initiation of breastfeeding and exclusive breastfeeding with the incidence of wasting at 6-24 months in the Working Area of ??the Langsa City Health Center UPTD. It is hoped that this study can increase mothers' knowledge regarding the risk of overweight or obesity in toddlers by knowing the impact of giving formula milk to babies